Improving Households Knowledge and Attitude on Water, Sanitation, and Hygiene Practices through School Health Programme in Nyakach, Kisumu County in Western Kenya. (10th November 2014) - Wasonga, Job; Olang'o, Charles Omondi; Kioli, Felix
Abstract : The global problem of access to improved sanitation and water management practices has been compounded by the gap existing between knowledge and practice as well as attitude. The aim of this study was to assess households' knowledge and attitude on water, sanitation, and hygiene practices through a school health programme. Semistructured questionnaires, focus group discussions, key informant interviews, and observation checklist were used to obtain information from 95 households which were systematically sampled. It was found that a school programme may not improve the gap between knowledge, attitude, and practice but may be good for future generations. This was found to be due to sociocultural issues which impede hygiene transformation. The implication is that health programmes must find innovative ways of bridging this gap in order to bring change in households through culture sensitive interventions.